Strengths perspective in assessing the expression of social skills of a person with moderate intellectual disability - Kaffemanienė, Irena; Jurevičienė, Margarita (Social Welfare: Interdisciplinary Approach, 2012)
The article contains case study of social skills of the moderately intellectually disabled person. This study complied with the view that social skills are a complex construct, which consists of integrating and complementary structural components, such as: 1) interaction skills; 2) communication skills; 3) participation skills; 4) emotional skills; and 5) social cognition skills; and each of these social skills’ structural components is constituted of complexes of social abilities. When identifying the social skills of a person with moderate intellectual disability, the concept of strengths perspective has been observed. Strengths perspective emphasizes the child’s capabilities (strengths), rather than the child’s inability. Scientifi c research problem could be defi ned in the following questions: what kind of social skills expression do the family members and pedagogues of a moderately intellectually disabled person notice? What strengths (available social skills) and problem areas do they identify?